2016
DOI: 10.4236/ojml.2016.62006
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Open Ended versus Closed Ended Questions in Turkish Classrooms

Abstract: Asking students good questions is a critical tool for developing their skills. In particular, open ended questions are believed to be useful for developing students' cognitive skills, as these questions encourage them to express and elaborate upon their thinking, and provide rationales for their thoughts (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
2
17
0
5
Order By: Relevance
“…For example, Lee and Kinzie's (2012) study pinpoints that open-ended questions pointed at reasoning and prediction were likely to generate students' responses illustrating cognition in a higher level. Besides, Çakır and Cengiz (2016) reveal that the opened-ended questions become an important means to involve children in conversations which are cognitively challenging and provoke higher-order thinking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee and Kinzie's (2012) study pinpoints that open-ended questions pointed at reasoning and prediction were likely to generate students' responses illustrating cognition in a higher level. Besides, Çakır and Cengiz (2016) reveal that the opened-ended questions become an important means to involve children in conversations which are cognitively challenging and provoke higher-order thinking.…”
Section: Discussionmentioning
confidence: 99%
“…The findings illustrated that the classroom interaction consisted of mostly yes/no questions and short-answer questions, followed by open-ended questions, display questions, and referential questions. Çakır and Cengiz (2016) conducted a study to see how a training program on open-ended questions motivated teachers to develop their classroom practice. The analysis showed that the training program encouraged teachers to apply a more systematic and reflective pedagogical practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although all these mentioned indicate correct uses, teachers further stated that they use divergent questions to determine whether students comprehend certain concepts, to activate their prior knowledge and to ensure that students express themselves. However, using convergent questions for the previously-mentioned purposes is easier and more reasonable (Bulent et al, 2016;Çakır & Cengiz, 2016). Therefore, based on the results of the study, the type of Batam elementary school teacher questions needs to be improved.…”
Section: Implementedmentioning
confidence: 99%